PENGARUH RASIO EPOKSI/AMPAS TEBU DAN PERLAKUAN ALKALI PADA AMPAS TEBU TERHADAP KEKUATAN BENTUR KOMPOSIT PARTIKEL EPOKSI BERPENGISI SERAT AMPAS TEBU - Akhmad Nadji Shabiri; Rizky Salaam Ritonga; M. Hendra S. Ginting (Talenta Publisher (Universitas Sumatera Utara), 2014)
This study was aimed to determine the effect of alkali treatment and fiber composition on the impact strength properties of epoxy composites filled with bagasse fiber. Composites are made by hand lay-up method by mixing epoxy and bagasse fiber with variation of volume ratio between matrix and filler are 100/0, 70/30, 60/40, and 50/50 (v / v) and the concentration of NaOH slolution in the alkali treatment are 0% , 1%, 2%, and 3%. Mechanical propertie tested was impact strengthand analized by SEM analysis. The results obtained from this study was the maximum impact strength value obtained of the composite was on the composition 70:30 with 2% NaOH concentration was 8,005 kJ/m2.